Myosin activity drives actomyosin bundle formation and organization in contractile cells of the Caenorhabditis elegans spermatheca - Wirshing, Alison C. E. (Mol Biol Cell, 2017)
Stress fibers—contractile actomyosin bundles—are important for cellular force production and adaptation to physical stress and have been well studied within the context of cell migration. However, less is known about actomyosin bundle formation and organization in vivo and in specialized contractile cells, such as smooth muscle and myoepithelial cells. The Caenorhabditis elegans spermatheca is a bag-like organ of 24 myoepithelial cells that houses the sperm and is the site of fertilization. During ovulation, spermathecal cells are stretched by oocyte entry and then coordinately contract to expel the fertilized embryo into the uterus. Here we use four-dimensional confocal microscopy of live animals to observe changes to spermathecal actomyosin network organization during cell stretch and contraction. Oocyte entry is required to trigger cell contraction and concomitant production of parallel actomyosin bundles. Actomyosin bundle size, connectivity, spacing, and orientation are regulated by myosin activity. We conclude that myosin drives actomyosin bundle production and that myosin activity is tightly regulated during ovulation to produce an optimally organized actomyosin network in C. elegans spermathecae.